Studies on mutagenic effectiveness and efficiency of gamma rays and its effect on quantitative traits in finger millet (Eleusine coracana L. Gaertn) - A.R. Ambavane; S.V. Sawardekar; S.A. Sawantdesai; N.B. Gokhale (Journal of Radiation Research and Applied Sciences, 2015)
Dry seeds (12% moisture) of two finger millet cultivar viz., Dapoli-1 and Dapoli Safed were irradiated with four doses of gamma-rays viz., 400 Gy, 500 Gy, 600 Gy and 700 Gy at BARC, Mumbai. In laboratory test, root and shoot lengths of seedlings were decreased with increase in dose of gamma rays. Similarly, germination percentage and survival rate of seedlings were decreased with increase in dose of gamma irradiation during field study. In M1 generation, three types of chlorophyll mutations viz., albino, xantha and viridis were observed. Albino and xantha were observed in all treatments, whereas, viridis observed only in lower doses viz., 400 Gy and 500 Gy. Based on the chlorophyll mutation frequency on M1 plants, mutagenic effectiveness and efficiency were computed. In Dapoli-1 variety, two early maturing mutants and three high yielding mutants were isolated from 500 Gy dose and 600 Gy dose, respectively. In M2 generation, the mutagenic treatments were effective in inducing various types of chlorophyll and morphological macro mutants, few of those show significant change in flowering, maturity and plant height character and few of them have good breeding value.